The effectiveness of selection process in government sector: a case study of Jabatan Audit Negara Cawangan Negeri Selangor / Nor Hidayat Ainudin - Ainudin, Nor Hidayat (Faculty of Business and Management, 2009)
From the topic that I’ve choose to make a research is for acknowledgement to the public to work in the government sector. This topic will tell us about how the effectiveness of the selection process in the government sector. This will expose about the selection process that has been taken by the government in recruiting the new employees to become the successful employees. During my practical training at Jabatan Audit Negara I’ve learn and know a few things about how the government hire their new employees to work in this sector. From what I know that it’s not easy for the public to work in the government sector because there are a lot of process they have to go through before they can accept as an employee in this sector. If the person has been accepted to work in the government sector their post is only contract worker for about one and a half year to work with the government sector. After they have finished the contract with the government sector it’s depends on that company whether the company want to take that employee as their permanent staff or not. This is difficult for that person to get work in the government sector because there are a lot of procedures that they have to follow. From the topic I can make a conclusion that to work in the government sector is not easy because the employee have to follow a steps for the process of recruitment that have been made by the government.